Aquatic center sewage reclamation and water reuse, using an integrated system combining adsorption, RO membrane system, and TiO2/Fe3O4 photocatalytic oxidation. Issue 1 (February 2021) - Izadpanah, M.; Sarrafzadeh, M.H.; Rezaei-DashtArzhandi, M.; Vojoudi, H.
Abstract: In the present research, reuse and recycling of aquatic center sewage (ACS), consisting of pool overflow, whirlpool tub regular discharge, sauna, and showers wastewater was evaluated using a fabricated hybrid system. The analysis was proposed to study the performance of a different combination of pretreatment, membrane filtration process, and photocatalytic oxidation (PO) to optimize the hybrid system. The thin-film nanocomposite (TFN) reverse osmosis (RO) membranes were prepared by the in situ interfacial polymerization process and TiO2 /Fe3 O4 nanocomposite photocatalyst (NCP) were synthesized by applying a chemical coprecipitation method. To characterize the properties of the fabricated TFN membranes, FESEM, EDX, zeta potential, and contact angle were performed, and FT-IR spectra and TEM images were also used for the TiO2 /Fe3 O4 nanocomposite characterization. In the designed hybrid system, four different types of TFN membranes and two different concentration of NCP were considered, and ACS composition before and after each stage was measured to determine the effectiveness of the employed processes. Accordingly, using the optimum TFN membrane and NCP dosage, the integrated system resulted in reducing almost all the measured pollutants to lower than the initial value in the influent feed water. Particularly reduction pertaining to chemical oxygen demand (COD) and turbidity showed to 99%, conductivity, nitrate, and ammonia were removed in excess than 85%, fecal coliform, phosphorus, turbidity, and total suspended solids (TSS) were entirely removed. Graphical Abstract: ga1 Highlights: The appropriate treatment setup was designed based on the quality of the sullage. The treatment train consists of pretreatment, TFN RO, and TiO2 /Fe3 O4 oxidation. Contaminants removal from sewage through different sections of the setup was assessed. The quality of treated water either reached the feed quality or even surpassed it.